SMU's Logo (Institutional Knowledge at Singapore Management University, 1999)
Press conference held at library@Orchard on 15 December 1999 to introduce Singapore Management University's new logo. Left to right: Associate Professor Tan Lee Chuan, Deputy President Tan Teck Meng, Chairman Ho Kwon Ping, Provost Tan Chin Tiong and Dean Tsui Kai Chong.